2021
DOI: 10.1080/23802359.2021.1914210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Aquilaria species with distribution records in China using DNA barcode technology

Abstract: Aquilaria species is one of the main plant resources that produce agarwood, which containing black resin with important economic and medicinal values. There are about 15 species known to the genus around the world, but only two can be found in China, i.e. A. sinensis and A. yunnanensis. In this study, A. sinensis and A. yunnanensis that endemic respectively to Hainan and Yunnan were sampled, on the basis of the investigation and observation of their main morphological features in plantation. Five primers, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“… 2017 ). Studies on chloroplast (cp) genome will provide molecular evidence for the species identification (Kang 2021 ). Here, the cp genome of A. cochinchinensis and A. dauricus was sequenced, assembled, and analyzed with related species, and it will be used to accurately molecular identification of these species.…”
mentioning
confidence: 99%
“… 2017 ). Studies on chloroplast (cp) genome will provide molecular evidence for the species identification (Kang 2021 ). Here, the cp genome of A. cochinchinensis and A. dauricus was sequenced, assembled, and analyzed with related species, and it will be used to accurately molecular identification of these species.…”
mentioning
confidence: 99%
“…Therefore, the more sensitive the marker, the more informative the cluster analysis results (Songa et al 2022). Combining several markers for phylogenetic analysis will increase the ability to identify different species (Tanaka and Ito 2019) and (Kang 2021). The problem is that markers might not always be used to differentiate within the species level.…”
Section: Morphological Characterization and Identificationmentioning
confidence: 99%
“…The aromatic agarwood properties have been used as fixative material (Santoso 2015) and raw materials in many consumer products (Lee et al 2016a). The agarwood has also been used in various religious events (Kang 2021) and illness treatments (i.e. as a sedative, carminative, and to relieve gastric problems, coughs, rheumatism, and high fever (Liu et al 2017), antibacterial and acetylcholinesterase inhibitory activities (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2005 ). It is reported that DNA barcode, a special DNA sequence used in species identification, has become a focus in biological taxonomy and species discrimination research in recent years (Kang 2021 ). But there are few DNA sequences are released for A. densiflorus in GenBank.…”
mentioning
confidence: 99%